2021
DOI: 10.1155/2021/9917302
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of the Prognostic Nutritional Index (PNI) in Patients with Severe COVID-19

Abstract: Background. The prognostic nutritional index (PNI) has been reported to significantly correlate with poor survival and postoperative complications in patients with various diseases, but its relationship with mortality in COVID-19 patients has not been addressed. Method. A multicenter retrospective study involving patients with severe COVID-19 was conducted to investigate whether malnutrition and other clinical characteristics could be used to stratify the patients based on risk. Results. A total of 395 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In that study, however, the authors did not study AKI as a reason for hypoalbuminemia but related that to inflammatory cascades and capillary permeability in severe cases of COVID-19 [ 24 ]. In contrast, other studies related hypoalbuminemia to nutritional index [ 25 ]. In our study, 21 patients (11%) who did not develop AKI, had hypoalbuminemia, and 2 of these patients died (p>0.05).…”
Section: Discussionmentioning
confidence: 97%
“…In that study, however, the authors did not study AKI as a reason for hypoalbuminemia but related that to inflammatory cascades and capillary permeability in severe cases of COVID-19 [ 24 ]. In contrast, other studies related hypoalbuminemia to nutritional index [ 25 ]. In our study, 21 patients (11%) who did not develop AKI, had hypoalbuminemia, and 2 of these patients died (p>0.05).…”
Section: Discussionmentioning
confidence: 97%
“…Since its initial validation, its predictive capabilities have been documented in various clinical scenarios, including oncology [ 23 ], cardiology [ 24 ], and critical care [ 25 ]. In the setting of COVID-19, previously published articles have reported that a lower PNI score was associated with a more severe disease form [ 26 , 27 ] and higher COVID-19-related mortality [ 28 , 29 , 30 ]. The two previously reported cut-off values for predicting mortality were slightly discrepant, as one study suggested a cut-off below 33.4 [ 28 ], and the other 42 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of COVID-19, previously published articles have reported that a lower PNI score was associated with a more severe disease form [ 26 , 27 ] and higher COVID-19-related mortality [ 28 , 29 , 30 ]. The two previously reported cut-off values for predicting mortality were slightly discrepant, as one study suggested a cut-off below 33.4 [ 28 ], and the other 42 [ 30 ]. Our study’s cut-off value with the best discriminative capabilities (AUROC of 0.77) was 28, significantly lower than the other values.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NLR of newly admitted patients was considered, the nutritional status of a patient varies according to the standard of living in different regions. Some studies have reported that malnutrition is an established risk factor for COVID-19 that demonstrates the strongest relationship with the NLR [ 53 , 54 ]. Considering the lack of unification in the NLR threshold, the value to determine the severity of COVID-19 needs to be considered depending on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%